SYNTHESIS OF 1, l1-DIHYDROXY-2,2'- (THIODIMETHYLENE) BIS-9(1 OH)-ANTHRONE (Journal of Sciences, Islamic Republic of Iran)
An efficient synthesis of the 1,l'-dihydroxy-2,2'-(thiodimethy1ene)bis-9(10H)- anthrone (5) is described. Reaction of 1 -methoxy-2-(bromomethy1)-9,lOanthraquinone (1) with excess sodium sulfide in ethanol, demethylation to the corresponding hydroxy and subsequent selective reduction produced the title compound in high yield.